Analysis of the Impact of Usury Practices on Economic Stability from an Islamic Perspective - Nisa, Chairun; Hamidah, Nazala Zalfa; Kusumawati, Nabila Dhea; Taufikurrahman, Taufikurrahman (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This article examines the usury (riba) concept from an Islamic perspective and its implications for economic systems and social life. Riba, which means